2013
DOI: 10.1111/faf.12032
|View full text |Cite
|
Sign up to set email alerts
|

China's distant‐water fisheries in the 21st century

Abstract: We conservatively estimate the distant-water fleet catch of the People's Republic of China for 2000-2011, using a newly assembled database of reported occurrence of Chinese fishing vessels in various parts of the world and information on the annual catch by vessel type. Given the unreliability of official statistics, uncertainty of results was estimated through a regionally stratified Monte Carlo approach, which documents the presence and number of Chinese vessels in Exclusive Economic Zones and then multiplie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 164 publications
(124 citation statements)
references
References 37 publications
3
115
1
1
Order By: Relevance
“…Given the conservative nature of this estimate, we extrapolated year long and estimated a number of 52 vessels in 2014. This number was multiplied by a CPUE of 1,200 t•boat −1 •year −1 , which is the minimum an illegal trawler catches to cover its operation costs (Pauly et al, 2014;Belhabib et al, 2015b). We assumed the illegal catch was constant between 2014 and 2015 and interpolated linearly between the estimate in 2010 (18,000 t), provided by Belhabib and Pauly (2015) for Guinea Bissau.…”
Section: Guinea Bissaumentioning
confidence: 99%
“…Given the conservative nature of this estimate, we extrapolated year long and estimated a number of 52 vessels in 2014. This number was multiplied by a CPUE of 1,200 t•boat −1 •year −1 , which is the minimum an illegal trawler catches to cover its operation costs (Pauly et al, 2014;Belhabib et al, 2015b). We assumed the illegal catch was constant between 2014 and 2015 and interpolated linearly between the estimate in 2010 (18,000 t), provided by Belhabib and Pauly (2015) for Guinea Bissau.…”
Section: Guinea Bissaumentioning
confidence: 99%
“…The Chinese modified their catch reports (∼10%) in response (42), but, even with these adjustments, catch from China often exceeds the combined catches of the next three largest fishing countries. It has also been suggested that China reports catches taken in other countries' waters as their own, artificially buoying Chinese catches (43,44), but it is difficult to explain why catch for some (often smaller, lower-value) species have increased while other (often larger, higher-value) species decreased if the catches are coming from other waters. Fishers generally target larger, high-value species when developing new fisheries (45).…”
Section: China's Fisheriesmentioning
confidence: 99%
“…In FAO region 71 (western central Pacific), only 12 % of China's landings were allocated to the Chinese EEZ. However, Chinese landings from FAO 71 were likely to be significantly underreported (Pauly et al 2013a), probably due to mis-reporting to FAO rather than an error in catch allocation. Since China's score was zero, reflecting landings that were over 200 % of the reference point, higher landings would likely still result in a lower score.…”
Section: Spatial Mapping Of Landingsmentioning
confidence: 99%